2019
DOI: 10.1186/s12866-019-1662-9
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of lyticase and β-glucosidase enzymes on biofilm degradation of Pseudomonas aeruginosa strains with different gene profiles

Abstract: BackgroundPseudomonas aeruginosa is a nosocomial pathogen that causes severe infections in immunocompromised patients. Biofilm plays a significant role in the resistance of this bacterium and complicates the treatment of its infections. In this study, the effect of lyticase and β-glucosidase enzymes on the degradation of biofilms of P. aeruginosa strains isolated from cystic fibrosis and burn wound infections were assessed. Moreover, the decrease of ceftazidime minimum biofilm eliminating concentrations (MBEC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…The obtained results conveyed that PtI works far better for E. coli biofilm eradication in comparison with the αA and Ec -PtI+αA. The role of the enzyme in anti-biofilm results directly depended on the composition and structure of the biofilm [ 24 ]. The slightly lower E. coli biofilm inhibition by Ec -PtI+αA compared to PtI might be due to the interference caused by αA catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results conveyed that PtI works far better for E. coli biofilm eradication in comparison with the αA and Ec -PtI+αA. The role of the enzyme in anti-biofilm results directly depended on the composition and structure of the biofilm [ 24 ]. The slightly lower E. coli biofilm inhibition by Ec -PtI+αA compared to PtI might be due to the interference caused by αA catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…These include various enzymes such as proteases, amylases, DNAses, β-glucosidases, and lyticases, etc. [ 5 , 19 , 23 , 24 , 25 ] The protease was found to be more effective compared to amylase for eliminating the Pseudomonas fluorescens biofilm [ 26 ]. Proteases are of many forms and are well-known as they hydrolyze the peptide bonds and degrade the proteins [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown the ability of different enzymes to disrupt biofilms in vitro and in vivo [10][11][12][13][14][15][16][40][41][42][43][44][45][46][47]. In the current study, we investigated the effectiveness of trypsin, β-PLOS ONE glucosidase, DNase I and combination of these enzymes on S. aureus-P. aeruginosa biofilms formed in WLM.…”
Section: Discussionmentioning
confidence: 99%
“…The recalcitrance of biofilms to antimicrobial agents is often attributed to the failure of these agents to penetrate the biofilm matrix. Moreover, clinical isolates of Candida and many filamentous fungi, including Aspergillus, Cladosporium, and Acremonium, have been shown to grow and form biofilm [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are various regimens of intracatheter retention regimens aiming for catheter preservation in fungal peritonitis, including amphotericin B and alcohol [ 10 , 11 ]; however, all were utilized in the patients without PD catheter obstruction. Lyticase, a combination of lytic enzymes endoglucanase and alkaline protease specific for disruption of fungal cell wall leading to cell lysis, has been used in-situ to treat candida and pseudomonal biofilms with impressive results [ [12] , [13] , [14] , [15] ]. We first report the effectiveness of the enzyme as adjunctive therapy in the salvation of the clogged PD catheter in patient with filamentous fungal peritonitis.…”
Section: Introductionmentioning
confidence: 99%